Predation on early life stages is decisive for year-class strength in the Barents Sea capelin ( Mallotus villosus ) stock. (11th October 2015) - Gjøsæter, Harald; Hallfredsson, Elvar H.; Mikkelsen, Nina; Bogstad, Bjarte; Pedersen, Torstein
Abstract: Year-class strength of Barents Sea capelin has been monitored closely since the early 1970s and during this ∼45 years period three short periods of almost total recruitment failure leading to three stock collapses have been observed. These events triggered much attention since there was a large commercial fishery for capelin, but also because of observed ecosystem effects attributed to the first of these collapse events. This attention motivated research to clarify mechanisms behind the recruitment failures, and many papers have been published regarding the causes of these events. Here, we review this literature and try to put the various investigations into context. Most of the research conducted gives evidence in favour of a hypothesis that was formulated after the first recruitment failure event in the mid-1980s that predation on capelin larvae was the main cause of recruitment failure. Most studies also support the hypothesis that young herring ( Clupea harengus ) was the main predator on capelin larvae, but other predators like young-of-the-year cod ( Gadus morhua ) and haddock ( Melanogrammus aeglefinus ) probably also played a role. Investigations of the effect of predators such as haddock, red king crab ( Paralithodes camtschaticus ), diving birds, and capelin on the demersal capelin eggs have also been reviewed. Usually, these predators are found to consume capelin eggs, but most likely not to an extent that would affect the recruitment to a noticeable degree. It is concluded that the predation on capelin larvae is the main reason for the observed recruitment failures, although predation from the predators reviewed here can hardly be the only reason for almost total recruitment failures observed in some periods.